2011
DOI: 10.3801/iafss.fss.10-213
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Study of the Properties of Smoke Particles Produced from both Flaming and Non-Flaming Combustion of Common Mine Combustibles

Abstract: This paper presents the results obtained from detailed studies of the properties of smoke particles produced from a wide range of flaming and non-flaming combustible materials and discusses how these properties impact early-warning fire detection as well as the hazards of smoke particle toxicity and reduced visibility that can significantly affect life safety. Data acquired include discrete angular scattering at wavelengths of 635 nm and 532 nm; visible light obscuration; light extinction at a wavelength of 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…These data provide a unique and complete description of the physical properties of the differing fractal aggregates generated from flaming and smoldering fires. It should be noted that when calculating the fractal properties using the UCB device, the Rg was calculated using average Rg / dg ratios obtained from a previous study [17]. Also, constant values were used for D f , where for aerosols generated from flaming fires, D f = 1.85 was used, while for aerosols generated from smoldering fires, D f = 2.1 was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data provide a unique and complete description of the physical properties of the differing fractal aggregates generated from flaming and smoldering fires. It should be noted that when calculating the fractal properties using the UCB device, the Rg was calculated using average Rg / dg ratios obtained from a previous study [17]. Also, constant values were used for D f , where for aerosols generated from flaming fires, D f = 1.85 was used, while for aerosols generated from smoldering fires, D f = 2.1 was used.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that ionization-type smoke detectors respond better to the smaller diameter particles produced from flaming combustion, while the photoelectric-type smoke detectors respond better to the larger diameter particles produced from smoldering combustion [2, 14, 15, 17, 21]. Additional research conducted by NIOSH reveals that the ionization-type detector also shows a high response to smaller particles produced from the exhausts of diesel engines, while the photoelectric type detector shows a much lower response [11].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the mechanisms of radar signal propagation through fire, it is necessary first to define what the actual physical content behind the general term “fire” is. As shown in [ 11 , 12 , 13 , 14 ], fire is composed of many different substances. For the most part, fire is a mixture of hot gases; the reaction also produces carbon dioxide, water vapour, light and heat.…”
Section: Microwave Propagation In Firementioning
confidence: 99%
“…Crews must make such decisions within minutes of fire discovery. Furthermore, while there is literature devoted to various measures that impact tenability, 14 there are few examples that take a comprehensive approach to tenability. The literature that does exist is largely outside of the US context and provides broad approaches without a methodology for determining tenability.…”
Section: Introductionmentioning
confidence: 99%